Preparation and Diagnosis of Atenolol And Amlodipine and Their Interactions With Some Medical Drugs - Mushrif, Ibtihal; Khaled, Fadhel; Farouk, Sherine (American Journal of Bioscience and Clinical Integrity, 2024)
Atenolol and salicylic acid are prepared by esterifying the reaction between salicylic acid and atenolol in the presence of an acidic catalyst, H2SO4Preparation of amlodipine with aspirin by esterification of aspirin chlorination and then its reaction with amlodipine. We identified the prepared and derived compounds using FT-IR, HNMR, and C13NMR techniques.